MAKNA FIGURATIF SENJATA DALAM IDIOM BAHASA ARAB (KAJIAN SEMANTIK) - Uki Sukiman (Adabiyyāt: Jurnal Bahasa dan Sastra, 2015)
This study aims to describe the meanings of idioms with weaponry elements in Arabic. The object of study is focused on the Arabic weaponry idiomatic expression. The theory of Semantic field is used to dissect the idiomatic elements. This is useful for finding relationships of meanings, which are formed by the use of elements of the weaponry idioms. The results shows that the weaponry idiomatic elements of guns have meanings mostly out of the war context. The Arabic weaponry idiomatic expression can show some positive and negative attributes, human activities and human relationships with others or with nature.